Indoor air quality audit and evaluation on thermal comfort in a school in Portugal - Pereira, Luísa Dias (2015)
Given the Portuguese national programme for rehabilitation of school buildings and the new regulations for thermal comfort and air quality in Portugal, whose demands contribute to increase energy costs, it became relevant to study a case before any refurbishment intervention, in order to assess the potential of different methods of actions and to improve results. It was also intended with this study to evaluate the indoor thermal quality and the indoor air quality experienced by the school occupants. From a practical case, a school in Coimbra, the procedure passed through the measurement of some environmental physical parameters [dry bulb temperature and relative humidity and the concentrations of chemical indicators, such as carbon monoxide and carbon dioxide]. Contributing to the indoor environment characterization, it was developed a survey directed to the occupants, in parallel with the measurements taken inside a classroom during a period in the heating season and another period in the ‘pre-cooling’ season. An estimation of the predicted percentage of dissatisfied and predicted mean vote comfort indices was done based on the school measured data. The results were compared with those obtained from the questionnaire. In the end, an analysis was also done based on CO2 concentration values.